2019
DOI: 10.3389/fphar.2018.01534
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Resveratrol as a Potent Chemoprotective and Synergistic Agent in Cancer Chemotherapy

Abstract: Background: Cancer has become a major disease endangering human health around the world. Conventional chemotherapy suffers from many side effects including pain, cardiotoxicity, hepatotoxicity, and renal toxicity. This review aims to describe a natural product of resveratrol as a chemoprotective and synergistic agent in the modulation of cancer chemotherapy.Methods: The publications were identified by comprehensive searching of SciFinder, PubMed, Web of Science, and our own reference library. Search terms incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
95
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(98 citation statements)
references
References 95 publications
1
95
0
2
Order By: Relevance
“…RES has been further studied for its increasing relevance in various neurological disorders, such as Alzheimer's [86][87][88], Parkinson's [89,90], and other neurodegenerative diseases [91,92], as well as brain tumors [93][94][95]. In addition, RES showed anticancer activity in many other cancer types, such as breast, prostate, skin, lung, liver, or colorectal cancer, as reviewed, for example, in [45,[96][97][98].…”
Section: Biological Effects Of Resveratrolmentioning
confidence: 99%
See 1 more Smart Citation
“…RES has been further studied for its increasing relevance in various neurological disorders, such as Alzheimer's [86][87][88], Parkinson's [89,90], and other neurodegenerative diseases [91,92], as well as brain tumors [93][94][95]. In addition, RES showed anticancer activity in many other cancer types, such as breast, prostate, skin, lung, liver, or colorectal cancer, as reviewed, for example, in [45,[96][97][98].…”
Section: Biological Effects Of Resveratrolmentioning
confidence: 99%
“…Numerous studies have shown that RES is able to alleviate the side effects induced by chemotherapeutic drugs [98,134]. Moreover, in combination with other anticancer agents, RES synergistically or additively enhances their efficacy against various types of cancer [135].…”
Section: Resveratrol and Standard Anticancer Therapymentioning
confidence: 99%
“…Trans-resveratrol (trans-3,5,4 -trihydroxystilbene, RSV) ( Figure 1) is a triphenolic phytoalexin with potent antioxidant activity and is found in a variety of plant species, such as grapevines, mulberries, peanuts, and the dried roots and stems of Japanese knotweed (Polygonum cuspidatum). An increasing volume of research on RSV has revealed its diverse range of biomedical properties, which may indicate its use for the treatment of a variety of human diseases [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Resveratrol has a variety of pharmacological effects including anti-inflammatory and antioxidant activities, along with inhibiting cancer growth and invasion. 13 In ovarian cancer, resveratrol inhibits cell survival in a time-dosedependent manner and is less toxic to normal cells. 14 A large number of studies have shown that resveratrol inhibits the initiation and progression of various tumors including breast cancer, prostate cancer, ovarian cancer, liver cancer, and lung cancer.…”
Section: Introductionmentioning
confidence: 99%